Production method for improving inclusion cracking of roll-formed high-strength steel

Through the denaturation of trace calcium elements in LF refining and RH vacuum treatment steps and the flow field control of continuous casting steps, the roll forming cracking caused by magnesium-aluminum spinel inclusions in high-strength steel is solved, significantly improving product quality and resistance Fatigue performance supports the high-quality and lightweight development of the automotive industry.

CN119287104APending Publication Date: 2025-01-10HANDAN IRON & STEEL GROUP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411347786.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the automotive industry, inclusion cracking often occurs during the roll forming process of high-strength steel, especially due to the existence of magnesium-aluminum spinel inclusions, the fatigue resistance of the material is affected, and the existing technology has not effectively solved this A question.

Method used

Using LF refining and RH vacuum treatment steps, the silicon element content in the steel is adjusted by adding trace calcium elements in ferrosilicon. The magnesium aluminum spinel with high melting point is a low melting point inclusion, and the continuous casting step is The tundra structure and plug rod blowing function control the removal of the molten steel flow field and inclusions, reducing the generation of high melting point inclusions.

Benefits of technology

Effectively reduce the generation rate of high melting point inclusions of ultra-high strength steel, reduce the incidence of long strip surface defects of the product, thereby improving product quality, significantly reducing the phenomenon of roll forming and cracking, and supporting the high level of the automotive industry. Development of lightweight quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287104A_ABST
    Figure CN119287104A_ABST
Patent Text Reader

Abstract

The invention discloses a production method for improving rolling forming high-strength steel inclusion cracking. The production method comprises the steps of LF refining, RH vacuum treatment and continuous casting. The LF refining step comprises the following steps: adding 30-35% of the total amount of silicon iron required by the LF in-station molten steel to reach the target silicon content of a finished product; and in the RH vacuum treatment step, the rest ferrosilicon in the total addition amount of the ferrosilicon is added. According to the method, inclusion denaturation in the LF refining process and the RH treatment process is adopted, the trace calcium element in silicon iron is fully utilized to achieve the inclusion denaturation effect, the generation probability of high-melting-point inclusions of the ultrahigh-strength steel is reduced, magnesium aluminate spinel type high-melting-point inclusions can be effectively reduced, and the product quality is improved; the occurrence rate of strip surface warping defects of the ultra-high strength steel product strip steel is reduced from 3.26% to 0.59%, and the cracking phenomenon caused by roll forming by customers is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgical production, in particular to a production method for improving inclusion cracking of roll-formed high-strength steel. Background Art

[0002] In order to actively respond to the national "dual carbon" goal and achieve green development, lightweighting, energy conservation and environmental protection in the automotive industry have become the goals pursued by major OEMs and supporting suppliers. At present, the lightweighting of automobiles continues to deepen, and the thinning of car bodies has become a development trend. As a result, high-strength steel and ultra-high-strength steel with lower yield strength, higher tensile strength and excellent fatigue performance are widely used in automobile A-pillars, B-pillars, anti-collision beams, seat slides, door guides and other parts, and their proportion in the whole vehicle is increasing year by year.

[0003] As the strength level of the material increases, the plasticity drops sharply, the one-time formability deteriorates, and the conventional stamping process is difficult to meet the requirements, so the roll forming process suitable for high-strength steel is adopted. However, due to the lightweight body and thinning of the material, cracking often occurs during the roll forming process, especially the cracking of inclusions caused by poor cleanliness of the molten steel seriously affects the fatigue resistance of the material.

[0004] By sampling typical samples at the cracks of the material, analysis showed that there were a large number of magnesia-alumina spinel-like granular foreign bodies formed by elements such as Mg, Al, and O at the defects. Magnesia-alumina spinel has a stable face-centered cubic structure, a high melting point (2130°C), high hardness, and is not easy to deform during rolling. Since magnesia-alumina spinel is relatively hard, it is easy to accumulate and clog at the head of the stopper rod or the inner wall of the immersed nozzle. As the flow field of the molten steel is unstable, the nodules can easily flow into the crystallizer and enter the product along with the ingot, inducing the risk of rolling inclusion cracking. At present, metallurgical scholars at home and abroad have done relatively little research on magnesia-alumina spinel in steel, and there are few reports on magnesia-alumina spinel inclusion defects in ultra-high-strength steel for automobiles.

[0005] The Chinese patent application number 202310970588.2 discloses a method for modifying inclusions in Ti microalloyed high-strength steel. This method modifies the original inclusions in the steel by adding ferrozirconium alloy during the RH refining process, improves the combination of Ti with O, N, and S, increases the effective Ti content in the steel, weakens the adverse effects of inclusions on steel toughness, and improves the plastic toughness of Ti microalloyed high-strength steel. However, no research has been conducted on the improvement and measures of magnesia-alumina spinel inclusions.

[0006] The Chinese patent application with application number 202311406835.2 discloses 1000MPa grade hot-rolled high-strength steel and its preparation method, which optimizes the chemical composition, uses continuous casting light pressure reduction, controls the temperature of the ingot entering the furnace and the hot rolling temperature, etc. However, the control of inclusions is not involved.

[0007] The paper "Research Status and Development of Magnesium Aluminum Spinel Inclusions in Steel" describes the background of the generation of MgAl2O4 inclusions, summarizes the research status of MgAl2O4 inclusions in steel, and proposes that further research is needed on the kinetics of the transformation of MgAl2O4 inclusions into low-melting-point composite oxide inclusions. However, no further research has been done on the key process parameters of continuous casting.

[0008] The paper "Thermodynamic Relationship between Magnesium Refractories and the Formation of Magnesium-aluminum Spinel Inclusions in Steel" analyzes the causes of spinel oxides formed in molten steel during the experiment from a thermodynamic perspective. However, it does not involve any other factors that cause spinel and optimization measures.

[0009] The paper "The Influence of Slag-Steel Reaction on the Formation of Lower Melting Point Non-metallic Inclusions in High-Strength Alloy Structural Steel" conducted laboratory research on the interaction between slag-molten steel-inclusions, and analyzed the mechanism of the transformation of high-melting point inclusions to low-melting point inclusions; however, it did not involve much control of the actual process parameters in steelmaking production.

[0010] The above patents and papers only analyze the causes and formation mechanisms of magnesium-aluminum spinel inclusion defects, but do not conduct much research on the improvement and optimization measures of the defects. Summary of the invention

[0011] The technical problem to be solved by the present invention is to provide a production method for improving inclusion cracking of roll-formed high-strength steel to improve product quality.

[0012] In order to solve the above technical problems, the technical solution adopted by the present invention is: it includes LF refining, RH vacuum treatment and continuous casting steps;

[0013] The LF refining step includes adding 30-35% of the total amount of ferrosilicon required for the LF incoming molten steel to reach the target silicon content of the finished product;

[0014] The RH vacuum treatment step: adding the remaining ferrosilicon in the total amount of the ferrosilicon.

[0015] Furthermore, in the RH vacuum treatment step, the vacuum treatment time is 25 to 32 minutes and the vacuum degree is less than 1.0 mbar.

[0016] Furthermore, in the RH vacuum treatment step, pure degassing and blowing are performed for 7 to 13 minutes after the RH is broken.

[0017] Furthermore, in the continuous casting step, the continuous casting tundish adopts a retaining wall dam structure, the tundish tonnage is ≥36 tons, and the plug rod argon blowing function in the tundish is turned on.

[0018] Furthermore, in the continuous casting step, the remaining steel amount is required to be 3 to 6 tons after the ladle pouring is completed.

[0019] The design idea of ​​the present invention is to take samples from the cracks of high-strength steel and analyze the defects to find a large number of magnesia-alumina spinel inclusions formed by elements such as Mg, Al, and O. Since magnesia-alumina spinel has a high melting point (2130°C) and high hardness, it is easy to accumulate and clog the plug head or the inner wall of the immersion nozzle. The nodules are very easy to flow into the crystallizer along with the ingot into the product due to the unstable flow field of the molten steel, and it is not easy to deform during rolling, which induces the risk of roller-pressed inclusion cracking.

[0020] The present invention makes full use of trace calcium in ferrosilicon to modify inclusions. Ordinary ferrosilicon contains about 1.64% calcium. Ferrosilicon is added in LF refining and RH steps to adjust the silicon content in molten steel and modify high-melting-point inclusions of magnesia-alumina spinel in the molten steel into low-melting-point inclusions.

[0021] The beneficial effects of the above technical solution are as follows: the present invention reduces the probability of high-melting-point inclusions in ultra-high-strength steel by denaturing inclusions during LF refining and RH treatment, making full use of trace calcium in ferrosilicon to denature inclusions, and can effectively reduce high-melting-point inclusions such as magnesium-aluminum spinel, thereby improving product quality; the incidence of long strip peeling defects on the surface of the resulting ultra-high-strength steel strip is reduced from 3.26% to 0.59%, and the cracking phenomenon caused by roll forming by customers is greatly reduced; it has contributed to the high-quality and lightweight development of the automotive industry and won wide acclaim from the society.

[0022] The present invention further controls key process points such as RH vacuum and pure degassing time control, continuous casting control, tundish structure optimization, stopper rod argon blowing, and residual steel operation at the end of ladle pouring, so that the continuous casting castability is significantly improved, the crystallizer liquid level fluctuation is significantly improved, and the occurrence rate of long strip peeling defects on the surface of the product strip after rolling is greatly reduced, thereby further improving the product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0024] Figure 1 This is a real picture of the surface of the high-strength steel hot-rolled coil obtained by conventional methods;

[0025] Figure 2 This is a real picture of the surface of high-strength steel roll forming obtained by conventional methods;

[0026] Figure 3 This is a real picture of the surface of the high-strength steel hot-rolled coil obtained in Example 1 of the present invention;

[0027] Figure 4 This is a real picture of the roll-formed surface of the high-strength steel obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The production method for improving inclusion cracking of roll-formed high-strength steel is applicable to high-strength steel and ultra-high-strength steel, and is particularly applicable to roll-formed ultra-high-strength steel for automobiles, and includes LF refining, RH vacuum treatment and continuous casting steps; the processes of each step are as follows:

[0029] (1) LF refining step: According to the silicon content in the LF incoming molten steel and the target silicon content of the finished product, the total amount of ferrosilicon added required for the LF incoming molten steel to reach the target silicon content of the finished product is calculated; in the conventional process, all of the ferrosilicon added in the above total amount is added in the LF refining step; in the LF refining step of the present method, 30-35% of the total amount of ferrosilicon added is added, preferably 1 / 3 of the total amount of ferrosilicon added is added; the calculation formula for the total amount of ferrosilicon added is shown in formula (A):

[0030]

[0031] Where: W 成品 [Si]% is the target silicon content of the finished product, wt%; W LF进站 [Si]% is the silicon content in the molten steel entering the LF station, wt%.

[0032] (2) RH vacuum treatment step: adding the remaining 65% to 70% of the ferrosilicon calculated in step (1) to the total amount of ferrosilicon added; vacuum treatment time 25 to 32 minutes, vacuum degree <1.0 mbar, so that high melting point inclusions can be fully denatured within the RH vacuum cycle treatment time, thereby improving the cleanliness of the molten steel; after RH breaking, pure degassing and clean blowing for 7 to 13 minutes is performed to promote the floating removal of inclusions in the molten steel.

[0033] (3) Continuous casting steps: Before continuous casting, the continuous casting machine is tested for roll gap accuracy to ensure that the opening deviation of the 1-10 sector segments is ≤ ±0.5 mm and the outer arc deviation is ≤ ±0.5 mm, so as to avoid large fluctuations in the liquid level during continuous casting caused by large deviations in the casting machine equipment accuracy and the risk of inclusion of the ingot induced by slag in the crystallizer.

[0034] Before the continuous casting, the tundish is preheated and baked. The temperature of the tundish is controlled at 800°C or less for 30 to 40 minutes before baking. Then the temperature is gradually increased to 1120 to 1150°C over 90 to 100 minutes, and the baking time is 130 to 140 minutes. Casting must be started within 10 minutes after the tundish is preheated and turned off.

[0035] The tundish is checked and cleaned before pouring to prevent the lining refractory from falling off; the tundish adopts a retaining wall dam structure, with a retaining wall height of 880mm and a dam height of 350mm. Three holes with a diameter of φ25mm are designed at equal distances at a horizontal line 81mm from the bottom of the dam, and the holes are inclined downward at an angle of 20°. In this way, the retaining wall dam is used to change the flow field of the molten steel in the tundish, eliminate the dead zone in the bottom area of ​​the tundish, and play a role in isolating the involved slag and promoting the floating removal of calcium aluminate inclusions.

[0036] The tonnage of the tundish is ≥36 tons, which ensures the residence time of the molten steel in the tundish and promotes the floating and removal of inclusions in the steel.

[0037] During the continuous casting process, the stopper rod argon blowing function is turned on, with the stopper rod argon blowing volume of 2.0-3.5L / min and the back pressure of 0.1-0.5bar. The stopper rod argon blowing function is used to reduce the accumulation and growth of small inclusions at the stopper rod head, thereby reducing the risk of inclusions falling off and inducing slag rolling caused by crystallizer liquid level fluctuation.

[0038] During the continuous casting process, 3 to 6 tons of steel are required to remain after each batch of ladle pouring. Slag discharge from the ladle is prohibited to prevent contamination of subsequent batches of molten steel.

[0039] Example 1: Six heats of high-strength steel are smelted in one pour. The Si content of the finished high-strength steel in this pour is required to be 0.5-0.6%.

[0040] (1) LF refining step: the amounts of ferrosilicon added were 221 kg, 198 kg, 252 kg, 231 kg, 205 kg and 223 kg respectively;

[0041] (2) RH vacuum treatment step: the amount of ferrosilicon added was 441kg, 379kg, 502kg, 459kg, 409kg, and 452kg, respectively. The vacuum treatment time was 28min, 26min, 25min, 31min, 29min, and 26min, respectively; the vacuum degree was 0.2mbar, 0.3mbar, 0.3mbar, 0.3mbar, 0.2mbar, and 0.4mbar, respectively. The pure degassing time after breaking the air was 8min, 11min, 7min, 10min, 8min, and 9min, respectively.

[0042] (3) Continuous casting steps: Before continuous casting, the accuracy of the equipment was checked. The opening deviation of the 1st to 10th sector segments was controlled within ±0.4 mm, and the outer arc deviation was controlled within ±0.5 mm. The accuracy of the casting machine equipment was well controlled.

[0043] The tundish is preheated and baked before continuous casting. The temperature is controlled at 790℃ for 35 minutes before preheating and baking, and then gradually heated to 1130℃ over 90 minutes. The baking time is 140 minutes. Continuous casting starts 8 minutes after the tundish is preheated and turned off.

[0044] Before pouring, the inside of the tundish was checked and found to be clean, with no loose or falling lining or debris inside the tundish.

[0045] The tundish adopts a retaining wall dam structure, with a retaining wall height of 880mm and a dam height of 350mm. Three holes with a diameter of φ25mm are designed at equal distances at a horizontal line 81mm away from the bottom of the dam, and the pores are inclined downward at a 20° angle.

[0046] The tonnage of the tundish during the continuous casting process is 38 tons, 36 tons, 42 tons, 40 tons, 39 tons and 38 tons respectively.

[0047] Before continuous casting starts, connect and check the stopper argon blowing pipeline. After continuous casting starts, turn on the stopper argon blowing function. The stopper argon blowing volume is 2.5L / min and the back pressure is 0.3bar.

[0048] The operation adopts large packages of leftover steel, and the quantities of leftover steel in large packages are 3 tons, 5 tons, 4 tons, 6 tons, 5 tons and 3 tons respectively.

[0049] (4) The actual surface appearance of the high-strength steel hot-rolled coil obtained by conventional method is shown in Figure 1 , the actual appearance of the roll forming surface is shown in Figure 2 ; The actual surface appearance of the high-strength steel hot-rolled coil steel in this embodiment is shown in Figure 3 , the actual appearance of the roll forming surface is shown in Figure 4 ;Depend on Figure 1-Figure 4 It can be seen that this embodiment effectively improves the surface quality of the strip steel and improves the surface quality after roll forming.

[0050] Example 2: Smelting 5 heats of high-strength steel in one pour, the Si content of the finished high-strength steel in this pour is required to be 0.15-0.25%.

[0051] (1) LF refining step: the amounts of ferrosilicon added were 90 kg, 85 kg, 92 kg, 81 kg and 95 kg respectively.

[0052] (2) RH vacuum treatment step: the amount of ferrosilicon added was 165kg, 160kg, 162kg, 172kg, and 160kg, respectively. The vacuum treatment time was 27min, 25min, 28min, 26min, and 32min, respectively; the vacuum degree was 0.4mbar, 0.6mbar, 0.2mbar, 0.3mbar, and 0.5mbar, respectively. The pure degassing time after breaking the air was 7min, 9min, 10min, 13min, and 8min, respectively.

[0053] (3) Continuous casting steps: Before continuous casting, the accuracy of the equipment was checked. The opening deviation of the 1st to 10th sector segments was controlled within ±0.4 mm, and the outer arc deviation was controlled within ±0.4 mm. The accuracy of the casting machine equipment was well controlled.

[0054] The tundish is preheated and baked before continuous casting. The temperature is controlled at 800℃ for 30 minutes before preheating and baking, and then gradually heated to 1150℃ over 100 minutes. The baking time is 135 minutes. Continuous casting starts 10 minutes after the tundish is preheated and turned off.

[0055] Before pouring, the inside of the tundish was checked and found to be clean, with no loose or falling lining or debris inside the tundish.

[0056] The tundish adopts a retaining wall dam structure, with a retaining wall height of 880mm and a dam height of 350mm. Three holes with a diameter of φ25mm are designed at equal distances at a horizontal line 81mm away from the bottom of the dam, and the pores are inclined downward at a 20° angle.

[0057] The tonnage of the tundish during the continuous casting process was 37 tons, 39 tons, 40 tons, 41 tons and 38 tons respectively.

[0058] Before continuous casting starts, connect and check the stopper argon blowing pipeline. After continuous casting starts, turn on the stopper argon blowing function. The stopper argon blowing volume is 3.5L / min and the back pressure is 0.5bar.

[0059] The operation adopts large packages of leftover steel, and the quantities of leftover steel in large packages are 4 tons, 3 tons, 5 tons, 4 tons and 6 tons respectively.

[0060] Embodiment 3: smelting 7 heats of high-strength steel in one pour, the Si content of the finished high-strength steel in this pour is required to be 0.45-0.55%.

[0061] (1) LF refining step: the amounts of ferrosilicon added were 199kg, 168kg, 183kg, 219kg, 196kg, 186kg and 211kg respectively.

[0062] (2) RH vacuum treatment step: the amount of ferrosilicon added was 392kg, 356kg, 362kg, 408kg, 401kg, 369kg, and 403kg, respectively. The vacuum treatment time was 27min, 25min, 28min, 32min, 26min, 25min, and 29min, respectively; the vacuum degree was 0.1mbar, 0.3mbar, 0.2mbar, 1.0mbar, 0.8mbar, 0.4mbar, and 0.5mbar, respectively. The pure degassing time after breaking the air was 7min, 8min, 13min, 10min, 9min, 10min, and 8min, respectively.

[0063] (3) Continuous casting steps: Before continuous casting, the accuracy of the equipment was checked. The opening deviation of the 1st to 10th sector segments was controlled within ±0.5 mm, and the outer arc deviation was controlled within ±0.5 mm. The accuracy of the casting machine equipment was well controlled.

[0064] The tundish was preheated and baked before continuous casting. The temperature was controlled at 780℃ for 40 minutes before preheating and baking, and then gradually heated to 1120℃ in 905 minutes. The baking time was 132 minutes. Continuous casting started 9 minutes after the tundish was preheated and turned off.

[0065] Before pouring, the inside of the tundish was checked and found to be clean, with no loose or falling lining or debris inside the tundish.

[0066] The tundish adopts a retaining wall dam structure, with a retaining wall height of 880mm and a dam height of 350mm. Three holes with a diameter of φ25mm are designed at equal distances at a horizontal line 81mm away from the bottom of the dam, and the pores are inclined downward at a 20° angle.

[0067] The tonnage of the tundish during the continuous casting process was 40 tons, 39 tons, 42 tons, 36 tons, 38 tons, 37 tons and 38 tons respectively.

[0068] Before continuous casting starts, connect and check the stopper argon blowing pipeline. After continuous casting starts, turn on the stopper argon blowing function. The stopper argon blowing volume is 2.0L / min and the back pressure is 0.1bar.

[0069] The operation adopts large packages of leftover steel, and the quantities of leftover steel in large packages are 3 tons, 5 tons, 6 tons, 4 tons, 4 tons, 3 tons and 6 tons respectively.

Claims

1. A production method for improving inclusion cracking of roll-formed high-strength steel, characterized in that: It includes LF refining, RH vacuum treatment and continuous casting steps; The LF refining step includes adding 30-35% of the total amount of ferrosilicon required for the LF incoming molten steel to reach the target silicon content of the finished product; The RH vacuum treatment step: adding the remaining ferrosilicon in the total amount of the ferrosilicon.

2. The production method for improving inclusion cracking of roll-formed high-strength steel according to claim 1, characterized in that: In the RH vacuum treatment step, the vacuum treatment time is 25 to 32 minutes, and the vacuum degree is less than 1.0 mbar.

3. The production method for improving inclusion cracking of roll-formed high-strength steel according to claim 1, characterized in that: In the RH vacuum treatment step, after the RH is broken, pure degassing and blowing are performed for 7 to 13 minutes.

4. A production method for improving inclusion cracking of roll-formed high-strength steel according to claim 1, 2 or 3, characterized in that: The continuous casting steps include: the continuous casting tundish adopts a retaining wall dam structure, the tundish tonnage is ≥36 tons, and the plug rod argon blowing function in the tundish is turned on.

5. A production method for improving inclusion cracking of roll-formed high-strength steel according to claim 1, 2 or 3, characterized in that: In the continuous casting step, the remaining steel amount is required to be 3 to 6 tons after the ladle pouring is completed.

Citation Information

Patent Citations

  • Method for modifying inclusions in Ti microalloyed high-strength steel

    CN116770017A

  • 1000MPa-grade hot-rolled high-strength steel and preparation method thereof

    CN117418166A